Association smooth-pole dual open-end windings permanent magnet synchronous machine with cascaded 2-level inverters for improved performances - Nayli, A.; Guizani, S.; Ben Ammar, F. (Національний технічний університет "Харківський політехнічний інститут", 2026)
Power segmentation is an increasingly important priority in high-power industrial drive applications that utilize AC machines. The authors propose a novel dual open-end windings permanent magnet synchronous machine. This machine reduces the required size of the power supply inverters while also improving dynamic performances and lifespan. Its power supply using 2-levels cascading inverters, further enhances these performances.

Сегментація потужності стає все більш важливим завданням у потужних промислових приводних системах, що використовують машини змінного струму. Автори пропонують нову синхронну машину з двома відкритими обмотками та постійними магнітами. Ця машина зменшує необхідні розміри інверторів живлення, одночасно покращуючи динамічні характеристики та термін служби. Її живлення із використанням дворівневих каскадних інверторів додатково підвищує ці характеристики.
Keywords: salient pole synchronous machines; cascaded 2-levels inverters; power segmentation; reliability; гладкополюсні синхронні машини; каскадні дворівневі інвертори; сегментація потужності; надійність